World Economic Outlook, April 2010 : Rebalancing Growth. (World Economic Outlook; World Economic Outlook ;, 2010)
The global economic recovery is progressing better than expected, but the speed of recovery varies, as outlined in the April 2010 World Economic Outlook. Some countries, notably in Asia, are off to a strong start, but growth in others is constrained by lasting damage to the financial sector and to household balance sheets. The challenge for policymakers is to ensure a smooth transition of demand, while maintaining supports that promote growth and employment. There is also a need to contain and reduce public debt and repair and reform the financial sector. This issue of the WEO also explores two other key challenges in the wake of the Great Recession: how to spur job creation in the face of likely high and persistent unemployment in advanced economies, and how countries that previously ran large current account surpluses or deficits can promote growth by rebalancing external and domestic demand.